Impact of mitochondrial dysfunction on the antitumor effects of immune cells - Wang, Quan; Yin, Xiangzhi; Huang, Xiaotong; Zhang, Lu; Lu, Haijun (Frontiers in Immunology, 2024)
Mitochondrial dysfunction, a hallmark of immune cell failure, affects the antitumor effects of immune cells through metabolic reprogramming, fission, fusion, biogenesis, and immune checkpoint signal transduction of mitochondria. According to researchers, restoring damaged mitochondrial function can enhance the efficacy of immune cells. Nevertheless, the mechanism of mitochondrial dysfunction in immune cells in patients with cancer is unclear. In this review, we recapitulate the impact of mitochondrial dysfunction on the antitumor effects of T cells, natural killer cells, dendritic cells, and tumor-associated macrophage and propose that targeting mitochondria can provide new strategies for antitumor therapy.